Analysis of Demographic Profile and Behavioral Gap in Sustainable Online Purchase: A Study of Indonesian Consumers - Asri Fianti Asmar; Muhammad Helmi; Linda Norhan; Herman Surdiatno Soegoto; Lilis Puspitawati (Journal Research of Social Science, Economics, and Management, 2026)
The increase in global environmental awareness has encouraged the emergence of the intention to buy eco-friendly products among digital consumers. However, the phenomenon of the gap between positive intentions (behavioral intention gap) and the realization of actual purchases is the main challenge in realizing sustainable consumption on e-commerce platforms. This research aims to analyze the demographic profile and characteristics of respondents' online shopping behavior in Indonesia and identify the factors that affect the gap. Using a descriptive quantitative approach, data was collected through an online questionnaire from 75 respondents of active e-commerce users. The frequency analysis showed that the majority of respondents were female (62.7%), over 40 years old (41.3%), S2 educated (49.3%), and working as civil servants (29.3%). Shopee is the main platform (77.3%) with a shopping frequency of 2-3 times per month (52.0%). These findings indicate that the potential segment of sustainable consumers is an adult group with higher education and economic stability. This study recommends the integration of personalized nudges features and simplification of sustainability information in e-commerce interfaces to convert intent into real purchase actions